1997
DOI: 10.1017/s0952523800008749
|View full text |Cite
|
Sign up to set email alerts
|

Is the input to a GABAergic or cholinergic synapse the sole asymmetry in rabbit's retinal directional selectivity?

Abstract: We examined contrast, direction of motion, and concentration dependencies of the effects of GABAergic and cholinergic antagonists, and anticholinesterases on responses to movement of On—Off directionally selective (DS) ganglion cells of the rabbit's retina. The drugs tested were curare and hexamethonium bromide (cholinergic antagonists), physostigmine (anticholinesterase), and picrotoxin (GABAergic antagonist). They all reduced the cells' directional selectivity, while maintaining their preferred-null axis. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
83
3

Year Published

1997
1997
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(97 citation statements)
references
References 56 publications
11
83
3
Order By: Relevance
“…For quite some time, they have been assumed to play an important role in the pathway leading to directionally selective ganglion cells, and several models on their contribution to directional selectivity have been proposed (see, e.g., Masland and Tauchi, 1986;Borg-Graham and Grzywacz, 1992). Most recently, the importance of starburst cells for the implementation of directional selectivity in the rabbit retinal ganglion cells has been questioned (Grzywacz et al, 1997;He and Masland, 1997), and the functional roles of this distinct amacrine cell type remain enigmatic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For quite some time, they have been assumed to play an important role in the pathway leading to directionally selective ganglion cells, and several models on their contribution to directional selectivity have been proposed (see, e.g., Masland and Tauchi, 1986;Borg-Graham and Grzywacz, 1992). Most recently, the importance of starburst cells for the implementation of directional selectivity in the rabbit retinal ganglion cells has been questioned (Grzywacz et al, 1997;He and Masland, 1997), and the functional roles of this distinct amacrine cell type remain enigmatic.…”
Section: Discussionmentioning
confidence: 99%
“…We assume the same ON/OFF dichotomy in tree shrew. Rabbit starburst cells costratify and synapse with directionally selective ganglion cells (Vaney et al, 1989;Famiglietti, 1992; for recent discussions of the functional effects, see Yang and Masland, 1992;Grzywacz et al, 1997;Kittila and Massey, 1997). The tree shrew also possesses directionally selective ganglion cells (van Dongen et al, 1976), but their morphology is not known, and it remains to be shown that they connect to the starburst cells.…”
Section: Chat Immunoreactivitymentioning
confidence: 99%
“…These amacrine cells contain both acetylcholine and GABA and thus could contribute to both the excitatory and inhibitory mechanisms (Vaney et al, 1989;Borg-Graham and Grzywacz, 1992;Grzywacz et al, 1997). The role of starburst cells within the direction-selective circuit is controversial, however, with one report claiming that they are critical (Yoshida et al, 2001) and another claiming that they are not essential (He and Masland, 1997).…”
Section: Implications For Synaptic Circuitrymentioning
confidence: 99%
“…He and Masland (1997) obtained clear evidence that the On-Off DS cells receive symmetrical input from surrounding cholinergic cells by using a laser to selectively ablate Cb amacrine cells located on either the preferred side of the ganglion cell or the opposite null side (see also Vaney et al, 2000). In contrast, Grzywacz et al (1997Grzywacz et al ( , 1998 have interpreted their own electrophysiological results as indicating that the On-Off DS cells receive strong input from cholinergic cells located on the preferred side and weak input from cholinergic cells located on the null side. In support of this conclusion, the authors cite abstracts of a morphological study showing that "the amount of dendritic material in proximity to DS ganglion cells' dendrites is larger for preferred-side cholinergic cells than for nullside ones" (Amthor and Grzywacz, 1995;Grzywacz et al, 1995).…”
Section: Dendritic Plexus Of Cholinergic Amacrine Cellsmentioning
confidence: 99%